Workshop Bedah Buku Ghazwul Fikri: Pola Baru Menyerang Islam di LIDMI Kota Kendari - Havis Aravik (AKM, 2021)
The Ghazwul Fikri book review workshop: A New Pattern of Attacking Islam at LIDMI Kendari City was carried out in collaboration between the Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) and the Lingkar Dakwah Mahasiswa Indonesia (LIDMI) Kendari City which was held in three sessions, starting with 28 November, 9 December and 23 December 2020. The purpose of this activity is to provide understanding and knowledge about various wars of thought (Ghazwul Fikri) that can influence Muslim religious beliefs, so that they can deviate from the purity of religious teachings. This activity uses material presentation methods via zoom meetings, guidance and evaluation. The result of this workshop activity is that Muslims today face various threats and challenges from both internal and external to Muslims. The most serious threat is Ghazwul Fikri (war of thought), a new strategy used to destroy Islam with various models used such as fashion, food, fun, foundation, song, cinema, school, sex, and so on.